Characterization and properties of palm fiber filled unsaturated polyester composites - Nurul Izza, Abdul Hamid (Universiti Malaysia Perlis (UniMAP), 2014)
The research on characterization and properties of palm fiber (PF) filled unsaturated polyester (UP) was investigated. The composites were prepared by using hand lay up technique before cured on oven about 10 minutes at 90˚C. The effect of filler loading on mechanical, flexural properties and morphology of palm fiber filled UP composites was studied. The modulus of elasticity and flexural modulus of UP/PF composites increase with increasing palm fiber loading while decrease the tensile strength, flexural strength and elongation at break. Scanning electron microscopy (SEM) study on tensile fracture surface of UP/PF composites indicates that poor interfacial interaction between palm fiber and UP matrix with increasing filler loading. Different sizes of palm fiber composites show that the UP/PF composites with size 75 μm have higher tensile and flexural strength, elongation at break, modulus of elasticity and flexural modulus compared the composites with size 150 μm. The chemical treatment of palm fiber with oleoyl chloride, 4-dimethylaminopyridine (DMAP) and seawater was used to improved mechanical properties of composites. The effect of oleoyl chloride has increased the tensile and flexural strength, modulus of elasticity, flexural modulus except elongation at break of treated composites. The treated composites with DMAP exhibit higher tensile and flexural strength, modulus of elasticity, flexural modulus but lower elongation at break compared untreated composites. The treatment with seawater of palm fiber has increases tensile and flexural properties, except elongation at break of composites. The micrographs SEM showed the all treated composites have better interfacial interaction and adhesion between fiber and matrix. The change of functional group of treated composites was evidenced by FTIR spectroscopy analysis.